Politics of Deforestation Case Study of Cardamom Hills of Kerala - Marcus Moench (Economic and Political Weekly January 26, 1991, 1991)
The causes of deforestation in the Cardamom Hills in the Idukki district of Kerala can only be understood in the context of the relationship between ethnic and religious communities which greatly influenced migration, forest encroachment, and conflict over control of land. In this article a brief historical review is followed by specific developments in three periods, 1750 to 1860, 1860 to 1940 and 1940 to 1964. The author also focuses on the debate over land control conducted within and between states and communities which was a major force in shaping social relations in the High Ranges